Epistemology of Islamic Education in the View of Muhammad Sholeh Darat - Arbani, Wahid; Nasution, Khoiruddin; Hasyim, Dardiri (Journal Research of Social Science, Economics, and Management, 2022)
This study aims to be able to understand and apply educational values ??in Muhammad Sholeh Darat’s view, so that ongoing education becomes more meaningful, not capital-oriented and only material-oriented. The method used in this research is descriptive-explanative research, where the author tries to describe first how the basic construction of Islamic education epistemology, context and situation behind Muhammad Sholeh Darat. Based on the results of the epistemology of Muhammad Sholeh’s educational thought, it is carried out through three main elements, namely: riyadhoh (spiritual practice), maqamat (stages of ascent of Sufism), and ahwal (Sufism experience). Riyadhah is an exercise of the soul in truth and sincerity in the context of istiqomah in worshiping Allah SWT. The mental development carried out in this guidance process is as exemplified and carried out by the Prophet Muhammad SAW. There are three forms of riyadhoh that can be done by a student to know Allah SWT through three activities, namely; seek knowledge, be consistent with sunnah practices, and always keep time.